Relative impact of stand structure, tree composition and climate on mountain bird communities - Archaux, Frédéric Frederic; Bakkaus, Noémie Noemie (FOREST ECOLOGY AND MANAGEMENT, 2007)
To recommend forestry practices favourable to birds, we estimated the relative importance of stand structure (mean tree height, overstory and understory cover), stand composition (from pure conifer or broadleaved to mixed conifer-broadleaf stands) and climate (altitude, aspect) on mountain forest birds (Mont-Ventoux, southern French Alps and Giffre valley, northern French Alps). Studies were conducted on species richness in forest birds (separated into species preferring broadleaves, preferring conifers or indifferent) and in cavity nesters. Climate, structure and composition had roughly equivalent weights on mountain forest birds, but their relative importance depended on the species group. Due to very contrasted climatic conditions, bird communities were the richest at low elevations in the northern site and at high elevations in the southern site. The richness of many ecological groups increased log-linearly with mean tree height; however, a decrease was observed for certain ecological groups at the northern site for a tree height above ca. 20-25 m. Mixed conifer-broadleaf stands (Holm Oak, Downy Oak or Beech mixed with Scots or Laricio Pines on Mont-Ventoux; Beech or Beech with other broadleaves mixed with Spruce in the Giffre valley) did not have higher bird richness than pure stands. The negative impact of broadleaf presence on birds preferring conifers was not compensated for (Giffre valley), or barely so (Mont-Ventoux), by a corresponding positive impact on birds preferring broadleaves. Conifers do not appear to systematically support poorer bird communities than broadleaves; therefore, juxtaposing pure stands of different trees may be more sensible than insisting on mixed stands if such stands are hard to manage. Furthermore, the introduced Laricio Pine stands supported bird communities as rich as native Scots Pine stands on Mont-Ventoux. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: bird species richness; detectability; ecological groups; exotic trees; Forest management; mixed stands